Diagnosis of Dilated Cardiomyopathy: Patient Reaction and Adaptation—Case Study and Review of the Literature. (16th October 2016) - Solomou, Solomis; Stavrou, Maria; Marley, Justin
Abstract : Objective . Heart failure remains a major cause of morbidity and mortality. Given that heart failure generally has a chronic course, it is important to appreciate the impact it can have on the quality of life of patients and also their partners or family carers. Method . Questionnaires were given to a patient newly diagnosed with dilated cardiomyopathy, during his hospital admission, as well as after discharge. The responses are summarised and explored in the discussion section, where we used review of the literature to discuss the implications of a new diagnosis of heart failure. Results. The patient's responses to the questionnaires suggest certain anxieties that are part of his adaptation to the diagnosis of heart failure. Conclusion. Depression is a common comorbid condition in patients with heart failure. Various tools can be used to screen for depression in patients with heart failure. Both pharmacological and nonpharmacological options are available. Rapid evaluation of ongoing problems and active participation by a psychiatrist can ensure that the patient receives the best possible clinical care.